Femoral osteochondroma responsible for ischiofemoral impingement, bursitis, and secondary lipoma arborescens mimicking malignant transformation. (December 2019) - Schubert, Thomas; Navez, Marie; Galant, Christine; Docquier, Pierre-Louis; Acid, Souad; Lecouvet, Frédéric E
We present the case of a 53-year-old woman with a known history of hereditary multiple exostosis disease referred for further imaging work-up after ultrasound and computed tomography leading to the suspicion of malignant transformation of an osteochondroma (exostosis) located on the posteromedial aspect of the right proximal femur. Imaging examinations suggested an ischiofemoral impingement resulting in a secondary bursitis associated with the development of an internal lipoma arborescens. This rare association explained the complexity of the diagnosis. Magnetic resonance imaging (MRI) played a key role in correctly identifying this benign complication of the osteochondroma and in distinguishing those observations from a secondary exostotic chondrosarcoma. MRI findings were subsequently confirmed at surgery and pathological examination.